Subtypes of type I IFN differentially enhance cytokine expression by suboptimally stimulated CD4+ T cells. (9th October 2013) - Hillyer, Philippa; Raviv, Nataly; Gold, Doria M.; Dougherty, Danielle; Liu, Jie; Johnson, Teresa R.; Graham, Barney S.; Rabin, Ronald L.
<x xml:space="preserve">Abstract</x> Human type I interferons (IFNs) include IFN‐β and 12 subtypes of IFN‐α. During viral infection, infiltrating memory CD4+ T cells are exposed to IFNs, but their impact on memory T‐cell function is poorly understood. To address this, we pretreated PBMCs with different IFNs for 16 h before stimulation with Staphylococcus aureus enterotoxin B and measured cytokine expression by flow cytometry. IFN‐α8 and ‐α10 most potently enhanced expression of IFN‐γ, IL‐2, and IL‐4. Potency among the subtypes differed most at doses between 10 and 100 U/mL. While enhancement of IL‐2 and IL‐4 correlated with the time of preincubation with type I IFN, IFN‐γ production was enhanced best when IFN‐α was added immediately preceding or simultaneously with T‐cell stimulation. Comparison of T‐cell responses to multiple doses of Staphylococcus aureus enterotoxin B and to peptide libraries from RSV or CMV demonstrated that IFN‐α best enhanced cytokine expression when CD4+ T cells were suboptimally stimulated. We conclude that type I IFNs enhance Th1 and Th2 function with dose dependency and subtype specificity, and best when T‐cell stimulation is suboptimal. While type I IFNs may beneficially enhance CD4+ T‐cell memory responses to vaccines or viral pathogens, they may also enhance the function of resident Th2 cells and exacerbate allergic inflammation.